Chemical profiles and antimicrobial activities of plants utilized in Brazilian traditional medicine - Silva, Rafaela Souza; da Silva, Marcílio Wagner Fontes; Bezerra, Giselle Barbosa; Ramos, Clécio Souza (Eclética Química, 2021)
Medicinal plants are used for primary health care in many countries. In Brazil, there are hundreds of street markets selling a wide variety of herbs for medicinal purposes without quality control or scientific evidence; instead, their purported efficacy is based exclusively on empirical ethnobotanical knowledge. The present study evaluated the effectiveness of five medicinal plants widely utilized in Brazil to treat infections, as well as determined their chemical profiles. The results revealed that the five plants investigated (Anacardium occidentale L., Handroanthus impetiginosus Mart., Bumelia sartorum Sw., Zornia brasiliensis Vogel and Cnidosculus urens Pohl) demonstrated moderate to strong antimicrobial activity against most fungi and bacteria tested, principally for infections caused by gram-negative bacteria. The extracts of four plants exhibited MIC of 19.5 µg mL-1 against the bacterium Escherichia coli. The results also confirmed that these five traditional medicinal plants are efficient and inexpensive alternative sources of substances to treat infections. The samples of the commercially marketed plants did not have consistent chemical compositions in at least one type of HPLC, GC/MS, UV or 1H NMR analysis.